Prevalence of Non-Carious Cervical Lesions in Individuals who Undergo Orthodontic Surgery: A Cross-Sectional Study - Muhammad Tahir, Ali Maqbool, Sanam Baloch, Amrita, Piryanka, Muhammad Anique, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To examine the dispersal of NCCLs (non-carious cervical lesions) by tooth type. This research also aims to explore NCCLs’ prevalence in those patients who go through orthodontic surgery and the possible factors linked with it. Study design: A cross-sectional study Place and Duration: This study was conducted at Pakistan Medical Center Hyderabad from August 2021 to August 2022. Methodology: Overall, 162 individuals were involved in this research. Data from the patients were collected before and after the orthodontic surgery. The data include age, gender, number of sessions activated, facial pattern, retreatment, compensatory treatment, and angle’s malocclusion. Lateral intraoral pictures of every patient were taken from the left, right, and front. These pictures were clicked to see whether NCCLs are present or absent in every tooth and to evaluate the dispersal of non-carious cervical lesions in the teeth of every individual. To evaluate the relationship between each variable and NCCLs, Poisson regression analysis (multivariate and bivariate) with robust variance was used. The confidence interval was at 95% and significant p-value was less than 0.05. Results: The prevalence of NCCLs before orthodontic surgery was 23.01% and the prevalence of non-carious cervical lesions after orthodontic surgery was 31.09%. The most affected teeth were premolars along with incisors, first molars, and canines. It was found after the statistical analysis that the factor that affected the prevalence ratio was age. If orthodontic surgery was performed in adulthood, NCCLs were more prevalent. Conclusion: It was concluded that the most affected teeth by NCCLs were premolars. Moreover, age seems to influence the increasing prevalence of non-carious cervical lesions in those participants who go through orthodontic surgery in their adulthood. Keywords: premolars, non-carious cervical lesions, teeth, orthodontic surgery